TYPES OF WASTE GENERATED IN NABARI PAYAM SOUTH SUDAN. A CROSS-SECTIONAL STUDY - Aboor, Agaar Chep; Dr. Deng , Mubiru; Dr. Sendagi, Mohammed (Student’s Journal of Health Research Africa, 2024)
Background There is a dire need to create environmental education and awareness, practices, and knowledge in high schools to enhance environmental monitoring and management in the country for both present and future periods. The study aims to assess the types of waste generated in Nabari Payam, South Sudan. Methodology A cross-sectional survey, descriptive and explanatory design where quantitative and qualitative methods were adopted. A questionnaire and Focus group discussion were adopted and interviews for Key Informants. Data was analyzed descriptively using the Statistical Package for Social Sciences and thematic methods for quantitative and qualitative data. Results 197 (59.0%) were male and 137 (41.0%) were female. (47.9%) mentioned inorganic waste, 10 (3.0%) with recyclable waste, 53(15.9%) with solid waste, 100 (29.9%) organic waste, 4 (l .2%) for liquid waste and 4 (1.2%) of the respondents mentioned hazardous waste. Qualitative information also revealed that waste of different types was mixed since there were not enough storage facilities, and in some health centers, nothing was available to store waste generated. One participant said, “….. Here wastes are mixed despite the source and this is due to limited containers. Wastes are discarded together in open space outside the Payam and sometimes I could see the safety boxes are being burnt using kerosene”. Conclusion Inorganic and organic waste were the main types of waste generated followed by sharp objects and solid waste. The local people and authorities have limited capacity to manage waste generated per day and this affects the health and environmental aspects of the Payam. Recommendations Residents of Nabari Payam should reduce the generation of different types of waste most especially those that are more dangerous, especially if not well managed.